Dilemmas of pluralist democracy : autonomy vs. control - Dahl, Robert A., 1915-2014 (Yale University Press, 1982)
Annotation Like individuals, then, organizations ought to possess some autonomy, and at the same time they should also be controlled. Crudely stated, this is the fundamental problem of pluralist democracy. The purpose in this book is to explore the problem of pluralist democracy and some possible solutions.
Keywords: Democracy.; Cultural pluralism.; Associations, institutions, etc.; Public interest.; Cultural Diversity; Societies; Diversité culturelle.; Associations.; Intérêt public.; public interest.; POLITICAL SCIENCE -- Political Ideologies -- Democracy.; Cultural pluralism; Democracy; Public interest; Electronic book.